2009
DOI: 10.1007/s11259-009-9311-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of Peste des petits ruminants virus antibodies in various districts of Tanzania

Abstract: Despite the widespread prevalence of infection with Peste des petits ruminants virus (PPRV) in goats and sheep industry in Asia and sub-Saharan Africa, there have been few, if any, structured population-based studies examining the epidemiology of this infection in Tanzania. In this study, we investigated the seroprevalence, and risk factors, of Peste des petitis ruminants(PPR) in sheep and goat flocks from seven different geographical administration authorities (Ngorongoro, Monduli, Longido, Karatu, Mbulu, Sih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 21 publications
(22 reference statements)
9
63
2
Order By: Relevance
“…PPR was officially confirmed in Tanzania in 2008 and it was confined to the northern zone in districts bordering Kenya [10,11]. This follows the official confirmation of PPR in neighboring Kenya in 2007 [7].…”
Section: Introductionmentioning
confidence: 55%
“…PPR was officially confirmed in Tanzania in 2008 and it was confined to the northern zone in districts bordering Kenya [10,11]. This follows the official confirmation of PPR in neighboring Kenya in 2007 [7].…”
Section: Introductionmentioning
confidence: 55%
“…Clearly both lineages III and IV are circulating in the Sudan and further serological reports from the country have confirmed outbreaks of PPRV in Sudan (Osman et al, 2009;Saeed et al, 2010). Swai et al (2009) recently confirmed natural transmission of PPRV and circulation of virus within herds in Tanzania. In this study, serological detection methods were used to evaluate seroconversion among sheep and goat herds from seven different geographical regions in northern Tanzania.…”
Section: Africamentioning
confidence: 78%
“…In addition, we did not visit the same areas both years; the differences in seroprevalence could therefore have been due to geographical differences. Previous studies in northern Tanzania found an overall seroprevalence of 45.5% in 2008 [46] and 22.1% in 2008–2009 [21]. In southern Tanzania, in the Mtwara region bordering Mozambique, 31% of sampled small ruminants had antibodies to PPRV [47].…”
Section: Discussionmentioning
confidence: 99%